College physics - Serway, Raymond A. ([Place of publication not identifed] : Cengage Learning Asia Pte Ltd, 2013)
Physics algebra approach is written for a one year course in a introductory physics usually taken by students majoring in biology, the health profession and other disciplines including environmental, earth and social sciences and technical fields such as engineering and architecture. The Mathematical techniques used in this books include algebra, geometry and trigonometry but not calculus.
Chapter 1. Introduction -- Chapter 2. Motion in one Dimension -- Chapter 3. Vectors and Two-dimension -- Chapter 4. The Laws of Motion -- Chapter 5. Energy -- Chapter 6. Momentum and Collision -- Chapter 7. Rotational Motion and the Law of Gravity -- Chapter 8. Rotational Equilibrium and rotational Dynamics -- Chapter 9. Solids and Fluids -- Chapter 10. Thermal Physics -- Chapter 11. Energy in Thermal Process -- Chapter 12. The Laws of Thermodynamics -- Chapter 13. Vibrations and Waves -- Chapter 14. Sounds -- Chapter 15. Electric Forces and Electric Fields -- Chapter 16. Electric Energy and Capacitance -- Chapter 17. Current and Resistance -- Chapter 18. Direct-Current Circuits -- Chapter 19. Magnetism -- Chapter 20. Induced Voltages and Inductance -- Chapter 21. Alternating-Current Circuits and Electromagnetic Waves -- Chapter 22. Reflection and Refraction of Light -- Chapter 23. Mirrors and Lenses -- Chapter 24. Waves Optics -- Chapter 25. Optical Instruments -- Chapter 26. Relativity -- Chapter 27. Quantum Physics -- Chapter 28. Atomic Physics -- Chapter 29. Nuclear Physics -- Chapter 30. Nuclear Energy .
Includes bibliographical references and index.
Keywords: PHYSICS